The Role Of The Department Of Education And Culture In Preserving Local Culture In Bengkulu City - Oktaria, Nindia; Saputra , Harius Eko; IS , Tuti Handayani (Utami Publisher, 2025)
This study aims to analyze the role of the Department of Education and Culture in preserving local culture in Bengkulu City. The research applies a qualitative method with data collected through interviews and observations. The study involved five informants, consisting of two key informants and three supporting informants. The findings reveal that the Department of Education and Culture performs several major roles: first, formulating and implementing cultural policies through cultural data collection; second, fostering communities and traditional institutions through active communication with the Regional Customary Council, although financial support remains limited; third, preparing cultural management materials annually, despite weaknesses in reporting and follow-up systems; and fourth, preserving traditions and cultural values that are increasingly adopted by the younger generation, although globalization and modern lifestyles remain significant challenges. The study concludes that despite the active role of the Department of Education and Culture, cultural preservation efforts continue to face obstacles, particularly in terms of funding, strengthening cultural data, and community participation.